Optimized Quality of Color Image denoising using Convolution Neural Network - Dr. Asha Basumatary (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Color image denoising is a crucial task in image processing, aiming to recover clean images from noisy observations. Convolutional Neural Networks (CNNs) have emerged as powerful tools for this purpose due to their ability to learn complex image features. This paper proposes a novel CNN architecture specifically designed for optimized quality color image denoising.